2017
DOI: 10.1016/j.ijscr.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Round ligament varicosities diagnosed as inguinal hernia during pregnancy: A case report and series from two regional hospitals in Japan

Abstract: IntroductionRound ligament varicosities (RLV) are not well-known and they are usually caused by pregnancy. Although the groin swelling of RLV mimics an inguinal hernia, it is difficult to distinguish between them through clinical examination alone, and there have been few published reports on this topic, especially from Asia.Case presentationA 37-year-old Japanese woman complained of left groin swelling for 2 weeks at her 28th week of gestation of her first pregnancy. According to a physical examination, she h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…With regard to long-term consequences we found that with the exception of the coagulopathic patient discussed above, complaints and swelling subsided spontaneously within 4 weeks after childbirth. This supports the results from a previous publication and is in line with other authors' findings [2,7]. Ongoing swelling and complaints for an extended period of time after delivery may therefore warrant further examination to rule out other potentially previously undetected causes in affected women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With regard to long-term consequences we found that with the exception of the coagulopathic patient discussed above, complaints and swelling subsided spontaneously within 4 weeks after childbirth. This supports the results from a previous publication and is in line with other authors' findings [2,7]. Ongoing swelling and complaints for an extended period of time after delivery may therefore warrant further examination to rule out other potentially previously undetected causes in affected women.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study cohort RLV occurred predominantly in the right groin, followed by left and bilateral manifestations ( Table 3). Other authors found a higher prevalence on the left side [2,7]. The reasons for these variable findings and their underlying cause remain unclear and warrant future exploration.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…4 Once the suspicion was made, the recommended diagnostic algorithm was performed by Lechner et al and like Mine et al and Yonggang et al two recent Asian studies, present case was treated conservatively and under surveillance, remitting the symptomatology after the resolution of pregnancy in a period no longer than 4 weeks. 6,10,11…”
Section: Discussionmentioning
confidence: 99%
“…Groin masses can also be confusing in female patients. Round ligament varicosities have been mistaken for inguinal hernias in pregnancy, resulting in unnecessary surgery in a high-risk patient [6]. This further emphasizes the need for accurate interpretation of ultrasonography.…”
Section: Crimson Publishersmentioning
confidence: 99%